2017
DOI: 10.1002/pat.4201
|View full text |Cite
|
Sign up to set email alerts
|

Study of mechanical and tribological properties of nylon 66‐titanium dioxide microcomposite

Abstract: Nylon 66 microcomposites with various weight percentage of titanium dioxide (TiO 2 ) were prepared by a twin screw extruder and investigated for mechanical and tribological properties.Mechanical properties of the composite such as tensile strength/modulus, flexural strength/modulus, impact, and compressive strength first showed an increase up to 6 wt% TiO 2 followed by a decrease at higher filler loading. The value of heat deflection temperature increased with the increase in wt% of TiO 2 . Sliding wear tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…As a result, more and more researchers are interested in the research on the heat resistance of PA6. Lalit Guglani and and his co-works [4] studied the heat resistance temperature of PA66/TiO2 composite and found that the heat deflection temperature of PA66 was increased by 5℃ by the addition of TiO2 of 6%. M. Kodal and his co-works [5] studied the heat deflection temperature of PA6/Talc/Wollastonite composite and found that the heat deflection temperature of PA6 was increased by 24℃ by the addition of 20 talc/20 wollastonite.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, more and more researchers are interested in the research on the heat resistance of PA6. Lalit Guglani and and his co-works [4] studied the heat resistance temperature of PA66/TiO2 composite and found that the heat deflection temperature of PA66 was increased by 5℃ by the addition of TiO2 of 6%. M. Kodal and his co-works [5] studied the heat deflection temperature of PA6/Talc/Wollastonite composite and found that the heat deflection temperature of PA6 was increased by 24℃ by the addition of 20 talc/20 wollastonite.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the traditional melt blending based on the shear flow has a long thermo‐mechanical process, leading to serious breakage of glass fibers and greatly limiting its reinforcement. Thus, it plays an important key on final properties of PA/GF composites that a suitable processing technology can improve the fiber dispersion and retention length simultaneously 14‐17 …”
Section: Introductionmentioning
confidence: 99%
“…As a result, there is considerable research interest in the heat resistance of PA6 composites. Guglani and Gupta studied the heat resistance temperature of a PA66/TiO 2 composite and found that the HDT of PA66 was increased by 5°C by the addition of 6% TiO 2 . Kodal et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Oswal et al . synthesized a N‐(4‐carboxyphenyl) maleimide (CPMI)/methyl methacrylate (MMA) copolymer and CPMI homopolymer and found CPMI enhanced the initial decomposition temperature of the polymers, which they attributed to the thermal stability of the blends being improved by the five‐element ring . The above literature shows that NPMI and its copolymers have played a positive role in enhancing the thermal stability of polymers.…”
Section: Introductionmentioning
confidence: 99%